Flame-retardant polyoxyethylene composite solid electrolyte and preparation process thereof

Through the modification of β-cycloids and polypropylene, prepare a combination of flame retardant polyoxide composite solid electrolyte, which improves its ionic conductivity, tensile strength and flame retardant performance, solved the PEO solid-state electrolytic quality easy The problem of burning and low -electricity guidance.

CN119361811APending Publication Date: 2025-01-24KNOWJI (SHANGHAI) NEW ENERGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411215291.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In some application scenarios, PEO solid electrolytes are limited by their flammability and low ionic conductivity caused by their high crystallinity at room temperature.

Method used

By modified β-cyclic paste and polypropylene, it improves its compatibility with polymer matrix, and introduces scalp phosphate groups to prepare a combination of flame retardant polyoxide composite solid electrolyte.

Benefits of technology

Improve the ionic conductivity, stretch strength and overall flame retardant performance of composite solid electrolytes, and solve the problem of flammable and low -electrical conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361811A_ABST
    Figure CN119361811A_ABST
Patent Text Reader

Abstract

The invention discloses a flame-retardant polyoxyethylene composite solid electrolyte and a preparation process thereof, and relates to the technical field of solid electrolytes. Comprising the following steps: 1, mixing and stirring modified polyacrylonitrile, polyacrylonitrile and N, N-dimethylformamide, and putting the mixture into an electrostatic spinning machine to obtain a polyacrylonitrile fiber membrane; 2, mixing and stirring the modified beta-cyclodextrin, acetonitrile, polyoxyethylene, lithium perchlorate and succinonitrile to obtain a mixed solution; and 3, putting the polyacrylonitrile fiber membrane into a polytetrafluoroethylene mold, dropwise adding the mixed solution, and drying and demolding at 40 DEG C to obtain the composite solid electrolyte. The composite solid electrolyte has the beneficial effects that beta-cyclodextrin and polyacrylonitrile are modified, so that the compatibility of beta-cyclodextrin and polyacrylonitrile with a polymer matrix is improved, and the ionic conductivity and tensile strength of the composite solid electrolyte are improved. Meanwhile, the grafted spirocyclic phosphate group enables the overall flame retardance of the composite solid electrolyte to be improved to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid electrolytes, in particular to a flame-retardant polyethylene oxide composite solid electrolyte and a preparation process thereof. Background Art

[0002] Solid electrolytes are solid ion conductors that are widely used in the field of electrical energy storage, such as all-solid-state lithium batteries and electric vehicles. Their main advantages include safety, easy processing, recyclability, and a wide electrochemical window. Solid electrolytes have many advantages over traditional liquid organic solvent electrolytes. Among them, PEO (polyethylene oxide)-based polymer solid electrolytes have been widely studied and applied due to their excellent mechanical strength and chemical neutrality; at temperatures above its melting point (65°C), PEO exhibits high lithium ion conductivity; and PEO can form stable complexes with a variety of lithium salts, which enables it to increase lithium ion conductivity and reduce interfacial impedance when used as a substrate in a liquid-free solid electrolyte, which helps to improve the overall performance of the battery.

[0003] Although PEO solid electrolytes have significant advantages in improving battery safety and reducing the risk of leakage and explosion, their inherent flammability and low ionic conductivity due to high crystallinity at room temperature limit their use in certain application scenarios.

[0004] In summary, in order to solve the above problems, the present invention prepares a composite solid electrolyte. Summary of the invention

[0005] The object of the present invention is to provide a flame retardant polyethylene oxide composite solid electrolyte and a preparation process thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A preparation process of a flame-retardant polyethylene oxide composite solid electrolyte comprises the following steps:

[0008] Step 1: Mix polyacrylonitrile, modified polyacrylonitrile and N,N-dimethylformamide, stir for 12-15 hours, and place in an electrospinning machine to prepare a polyacrylonitrile fiber membrane;

[0009] Step 2: Mix the modified β-cyclodextrin, acetonitrile, polyethylene oxide, lithium perchlorate and succinonitrile, and stir for 12-15 hours to obtain a mixed solution;

[0010] Step 3: Place the polyacrylonitrile fiber membrane into a polytetrafluoroethylene mold, add the mixed solution dropwise, dry and demould at 40°C to obtain a composite solid electrolyte.

[0011] More optimally: the preparation process of the modified β-cyclodextrin is:

[0012] S1: Under a protective atmosphere, phosphorus oxychloride, pentaerythritol and anhydrous acetonitrile are mixed, the temperature is raised to 72-80°C, and the reaction is carried out for 6-8h to obtain intermediate A;

[0013] S2: (1) Mix intermediate A, triethylamine and toluene, and stir ultrasonically for 4-5 hours to obtain a mixed solution of intermediate A; (2) Slowly add polyethylene oxide to the mixed solution of intermediate A, heat to 70-80° C., and react for 5-8 hours to obtain intermediate B;

[0014] S3: (1) Mix β-cyclodextrin, triethylamine and distilled water, and stir ultrasonically for 1-2 hours to obtain a β-cyclodextrin mixed solution; (2) Mix intermediate B with toluene, and stir ultrasonically for 3-4 hours to obtain an intermediate B solution; (3) Heat the intermediate B solution to 75-80°C, slowly add the β-cyclodextrin mixed solution, and after the addition is complete, react for 3-4 hours to obtain modified β-cyclodextrin.

[0015] More optimally, the intermediate A comprises the following components: by weight, 10-12 parts of phosphorus oxychloride, 4-5 parts of pentaerythritol, and 40-50 parts of anhydrous acetonitrile; the intermediate B comprises the following components: by weight, 15-18 parts of intermediate A, 1-2 parts of triethylamine, 50-60 parts of toluene, and 6-8 parts of polyethylene oxide.

[0016] More optimally, the β-cyclodextrin mixed solution comprises the following components: by weight, 10-12 parts of β-cyclodextrin, 0.5-1 parts of triethylamine, and 50-60 parts of distilled water; the intermediate B solution comprises the following components: by weight, 15-20 parts of intermediate B and 60-65 parts of toluene.

[0017] More optimally: the preparation process of the modified polyacrylonitrile is as follows: (1) mixing polyacrylonitrile, ethylenediamine and deionized water, heating to 70-75°C, and reacting for 12-15 hours to obtain amino polyacrylonitrile; (2) mixing amino polyacrylonitrile, intermediate B, toluene and aluminum chloride, heating to 50-55°C, and reacting for 6-8 hours to obtain modified polyacrylonitrile.

[0018] More optimally, the amino polyacrylonitrile comprises the following components: by weight, 10-12 parts of polyacrylonitrile, 110-120 parts of ethylenediamine, and 500-550 parts of deionized water; the modified polyacrylonitrile comprises the following components: by weight, 8-10 parts of amino polyacrylonitrile, 4-5 parts of intermediate B, 50-55 parts of toluene, and 1-2 parts of aluminum chloride.

[0019] More optimally: the working parameters of the electrospinning machine are: voltage 15-18KV, needle and receiver 15-20cm, propulsion speed 0.3-0.5mL / h, drum speed 400-450r / min, temperature 30-35℃, humidity 30%-40%.

[0020] More optimally, the polyacrylonitrile fiber membrane comprises the following components: by weight, 10-12 parts of polyacrylonitrile, 3-4 parts of modified polyacrylonitrile, and 100-120 parts of N,N-dimethylformamide.

[0021] More optimally, the mixed solution comprises the following components: by weight, 0.5-0.8 parts of modified β-cyclodextrin, 100-110 parts of acetonitrile, 5-10 parts of polyethylene oxide, 0.1-0.2 parts of lithium perchlorate, and 0.8-1 parts of succinonitrile.

[0022] The present invention improves the compatibility of β-cyclodextrin and polyacrylonitrile with the polymer matrix by modifying them, thereby improving the ionic conductivity and tensile strength of the composite solid electrolyte. At the same time, the grafted spirocyclic phosphate groups also improve the overall flame retardancy of the composite solid electrolyte. The details are as follows:

[0023] First, the spirocyclic phosphate grafted with β-cyclodextrin has a good flame retardant effect and a stable six-membered heterocyclic structure. When burning, the pentaerythritol skeleton will form a coke protective layer to inhibit further combustion of the matrix, greatly improving the flame retardant properties of the matrix. At the same time, the introduction of polyethylene oxide segments into β-cyclodextrin improves the compatibility of β-cyclodextrin with the matrix, promotes the dissociation of lithium salts, increases the concentration of free lithium ions, and thus improves the ionic conductivity of the electrolyte;

[0024] Second, β-cyclodextrin can interfere with the regular arrangement of the chain segments of the polymer matrix, reduce the crystallinity of the polymer, increase the amorphous region, provide more transmission channels for lithium ions, reduce the obstacles to the migration of lithium ions in these regions, and thus improve the ionic conductivity of the electrolyte. At the same time, β-cyclodextrin, as a rigid nanofiller, can enhance the mechanical strength and toughness of the polymer matrix, improve the tensile strength of the electrolyte, and help prevent the formation of lithium dendrites;

[0025] Thirdly, polyacrylonitrile has high strength and rigidity, which can significantly improve the mechanical strength and tensile strength of the electrolyte. At the same time, the grafted polyethylene oxide segments and spirocyclic phosphate groups improve its compatibility with the matrix and further improve the overall flame retardancy of the composite solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a process flow chart for preparing the composite solid electrolyte. DETAILED DESCRIPTION

[0027] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0028] It should be noted that the following parts are parts by weight, and the purchase manufacturers of all raw materials involved in the present invention are exemplified without any special restrictions: in the following embodiments, phosphorus oxychloride CAS is 10025-87-3, and the purchase manufacturer is Shanghai Jinjinle Industrial Co., Ltd.; pentaerythritol CAS is 15-77-5; β-cyclodextrin CAS is 7585-39-9, and the purchase manufacturer is Hubei Yongkuo Technology Co., Ltd.; polyethylene oxide CAS is 68441-17-8, and the purchase manufacturer is Hubei Yongkuo Technology Co., Ltd.; polyacrylonitrile CAS is 25014-41-9, and the purchase manufacturer is Hubei Yongkuo Technology Co., Ltd.; N,N-dimethylformamide CAS is 68-12-2, and the purchase manufacturer is Shanghai Jinjinle Industrial Co., Ltd.; lithium perchlorate CAS is 7791-03-9; succinonitrile CAS is 110-61-2, and the purchase manufacturer is Shanghai Jinjinle Industrial Co., Ltd.

[0029] Example 1: A process for preparing a flame-retardant polyethylene oxide composite solid electrolyte, comprising the following steps:

[0030] Pre-preparation: The preparation process of modified β-cyclodextrin is:

[0031] S1: Under nitrogen atmosphere, 10 parts of phosphorus oxychloride, 4 parts of pentaerythritol, and 40 parts of anhydrous acetonitrile were mixed, the temperature was raised to 72°C, and the reaction was carried out for 6 hours to obtain intermediate A;

[0032] S2: (1) 15 parts of intermediate A, 1 part of triethylamine and 50 parts of toluene were mixed and ultrasonically stirred for 4 hours to obtain a mixed solution of intermediate A; (2) 6 parts of polyethylene oxide were slowly added to the mixed solution of intermediate A, the temperature was raised to 70°C, and the reaction was carried out for 5 hours to obtain intermediate B;

[0033] S3: (1) Mix 10 parts of β-cyclodextrin, 0.5 parts of triethylamine and 50 parts of distilled water, and stir ultrasonically for 1 hour to obtain a β-cyclodextrin mixed solution; (2) Mix 15 parts of intermediate B with 60 parts of toluene, and stir ultrasonically for 3 hours to obtain an intermediate B solution; (3) Heat the intermediate B solution to 75°C, slowly add the β-cyclodextrin mixed solution, and after the addition is complete, react for 3 hours to obtain modified β-cyclodextrin.

[0034] Pre-preparation: The preparation process of modified polyacrylonitrile is:

[0035] (1) 10 parts of polyacrylonitrile, 110 parts of ethylenediamine and 500 parts of deionized water were mixed, heated to 70°C, and reacted for 12 hours to obtain amino polyacrylonitrile; (2) 8 parts of amino polyacrylonitrile, 4 parts of intermediate B, 50 parts of toluene and 1 part of aluminum chloride were mixed, heated to 50°C, and reacted for 6 hours to obtain modified polyacrylonitrile.

[0036] Step 1: 10 parts of polyacrylonitrile, 3 parts of modified polyacrylonitrile, and 100 parts of N,N-dimethylformamide were mixed, stirred for 12 hours, and placed in an electrospinning machine. The parameters were set as follows: voltage 15KV, 15 cm between the needle and the receiver, propulsion speed 0.3mL / h, drum speed 400r / min, temperature 30°C, to prepare a polyacrylonitrile fiber membrane;

[0037] Step 2: 0.5 parts of modified β-cyclodextrin, 100 parts of acetonitrile, 5 parts of polyethylene oxide, 0.1 parts of lithium perchlorate, and 0.8 parts of succinonitrile were mixed and stirred for 12 hours to obtain a mixed solution;

[0038] Step 3: Place the polyacrylonitrile fiber membrane into a polytetrafluoroethylene mold, add the mixed solution dropwise, dry and demould at 40°C to obtain a composite solid electrolyte.

[0039] Example 2: A process for preparing a flame-retardant polyethylene oxide composite solid electrolyte, comprising the following steps:

[0040] Pre-preparation: The preparation process of modified β-cyclodextrin is:

[0041] S1: Under nitrogen atmosphere, 10 parts of phosphorus oxychloride, 4 parts of pentaerythritol, and 40 parts of anhydrous acetonitrile were mixed, the temperature was raised to 80°C, and the reaction was carried out for 8 hours to obtain intermediate A;

[0042] S2: (1) 15 parts of intermediate A, 1 part of triethylamine and 50 parts of toluene were mixed and ultrasonically stirred for 5 hours to obtain a mixed solution of intermediate A; (2) 8 parts of polyethylene oxide were slowly added to the mixed solution of intermediate A, the temperature was raised to 80°C, and the reaction was carried out for 8 hours to obtain intermediate B;

[0043] S3: (1) Mix 12 parts of β-cyclodextrin, 1 part of triethylamine and 60 parts of distilled water, and stir ultrasonically for 2 hours to obtain a β-cyclodextrin mixed solution; (2) Mix 20 parts of intermediate B with 65 parts of toluene, and stir ultrasonically for 4 hours to obtain an intermediate B solution; (3) Heat the intermediate B solution to 80°C, slowly add the β-cyclodextrin mixed solution, and after the addition is complete, react for 4 hours to obtain modified β-cyclodextrin.

[0044] Pre-preparation: The preparation process of modified polyacrylonitrile is:

[0045] (1) 12 parts of polyacrylonitrile, 120 parts of ethylenediamine, and 550 parts of deionized water were mixed, heated to 75°C, and reacted for 15 hours to obtain amino polyacrylonitrile; (2) 10 parts of amino polyacrylonitrile, 5 parts of intermediate B, 55 parts of toluene, and 2 parts of aluminum chloride were mixed, heated to 55°C, and reacted for 8 hours to obtain modified polyacrylonitrile.

[0046] Step 1: 12 parts of polyacrylonitrile, 4 parts of modified polyacrylonitrile, and 120 parts of N,N-dimethylformamide were mixed, stirred for 15 hours, and placed in an electrospinning machine. The parameters were set as follows: voltage 15KV, needle and receiver 15cm, propulsion speed 0.3mL / h, drum speed 400r / min, temperature 30°C, to prepare a polyacrylonitrile fiber membrane;

[0047] Step 2: 0.8 parts of modified β-cyclodextrin, 110 parts of acetonitrile, 10 parts of polyethylene oxide, 0.2 parts of lithium perchlorate, and 1 part of succinonitrile were mixed and stirred for 15 hours to obtain a mixed solution;

[0048] Step 3: Place the polyacrylonitrile fiber membrane into a polytetrafluoroethylene mold, add the mixed solution dropwise, dry and demould at 40°C to obtain a composite solid electrolyte.

[0049] Example 3: A process for preparing a flame-retardant polyethylene oxide composite solid electrolyte, comprising the following steps:

[0050] Pre-preparation: The preparation process of modified β-cyclodextrin is:

[0051] S1: Under nitrogen atmosphere, 10 parts of phosphorus oxychloride, 4 parts of pentaerythritol, and 40 parts of anhydrous acetonitrile were mixed, the temperature was raised to 75°C, and the reaction was carried out for 7 hours to obtain intermediate A;

[0052] S2: (1) 15 parts of intermediate A, 1 part of triethylamine and 50 parts of toluene were mixed and ultrasonically stirred for 4.5 hours to obtain a mixed solution of intermediate A; (2) 7 parts of polyethylene oxide were slowly added to the mixed solution of intermediate A, the temperature was raised to 75°C, and the reaction was carried out for 6 hours to obtain intermediate B;

[0053] S3: (1) Mix 11 parts of β-cyclodextrin, 0.8 parts of triethylamine and 55 parts of distilled water, and stir ultrasonically for 1.5 hours to obtain a β-cyclodextrin mixed solution; (2) Mix 18 parts of intermediate B and 62 parts of toluene, and stir ultrasonically for 3.5 hours to obtain an intermediate B solution; (3) Heat the intermediate B solution to 78°C, slowly add the β-cyclodextrin mixed solution, and after the addition is complete, react for 3.5 hours to obtain modified β-cyclodextrin.

[0054] Pre-preparation: The preparation process of modified polyacrylonitrile is:

[0055] (1) 11 parts of polyacrylonitrile, 115 parts of ethylenediamine and 520 parts of deionized water were mixed, heated to 72°C, and reacted for 13 hours to obtain amino polyacrylonitrile; (2) 9 parts of amino polyacrylonitrile, 4.5 parts of intermediate B, 52 parts of toluene and 1.5 parts of aluminum chloride were mixed, heated to 52°C, and reacted for 7 hours to obtain modified polyacrylonitrile.

[0056] Step 1: 11 parts of polyacrylonitrile, 3.5 parts of modified polyacrylonitrile, and 110 parts of N,N-dimethylformamide were mixed, stirred for 13 hours, and placed in an electrospinning machine. The parameters were set as follows: voltage 15KV, needle and receiver 15cm, propulsion speed 0.3mL / h, drum speed 400r / min, temperature 30°C, to prepare a polyacrylonitrile fiber membrane;

[0057] Step 2: 0.6 parts of modified β-cyclodextrin, 105 parts of acetonitrile, 8 parts of polyethylene oxide, 0.15 parts of lithium perchlorate, and 0.9 parts of succinonitrile were mixed and stirred for 13 hours to obtain a mixed solution;

[0058] Step 3: Place the polyacrylonitrile fiber membrane into a polytetrafluoroethylene mold, add the mixed solution dropwise, dry and demould at 40°C to obtain a composite solid electrolyte.

[0059] Example 4: A process for preparing a flame-retardant polyethylene oxide composite solid electrolyte, comprising the following steps:

[0060] Pre-preparation: The preparation process of modified β-cyclodextrin is:

[0061] S1: Under nitrogen atmosphere, 10 parts of phosphorus oxychloride, 4 parts of pentaerythritol, and 40 parts of anhydrous acetonitrile were mixed, the temperature was raised to 72°C, and the reaction was carried out for 6 hours to obtain intermediate A;

[0062] S2: (1) 15 parts of intermediate A, 1 part of triethylamine and 50 parts of toluene were mixed and ultrasonically stirred for 4 hours to obtain a mixed solution of intermediate A; (2) 6 parts of polyethylene oxide were slowly added to the mixed solution of intermediate A, the temperature was raised to 70°C, and the reaction was carried out for 5 hours to obtain intermediate B;

[0063] S3: (1) Mix 12 parts of β-cyclodextrin, 1 part of triethylamine and 60 parts of distilled water, and stir ultrasonically for 2 hours to obtain a β-cyclodextrin mixed solution; (2) Mix 20 parts of intermediate B with 65 parts of toluene, and stir ultrasonically for 4 hours to obtain an intermediate B solution; (3) Heat the intermediate B solution to 80°C, slowly add the β-cyclodextrin mixed solution, and after the addition is complete, react for 4 hours to obtain modified β-cyclodextrin.

[0064] Pre-preparation: The preparation process of modified polyacrylonitrile is:

[0065] (1) 10 parts of polyacrylonitrile, 110 parts of ethylenediamine and 500 parts of deionized water were mixed, heated to 70°C, and reacted for 12 hours to obtain amino polyacrylonitrile; (2) 8 parts of amino polyacrylonitrile, 4 parts of intermediate B, 50 parts of toluene and 1 part of aluminum chloride were mixed, heated to 50°C, and reacted for 6 hours to obtain modified polyacrylonitrile.

[0066] Step 1: 12 parts of polyacrylonitrile, 4 parts of modified polyacrylonitrile, and 120 parts of N,N-dimethylformamide were mixed, stirred for 15 hours, and placed in an electrospinning machine. The parameters were set as follows: voltage 15KV, needle and receiver 15cm, propulsion speed 0.3mL / h, drum speed 400r / min, temperature 30°C, to prepare a polyacrylonitrile fiber membrane;

[0067] Step 2: 0.6 parts of modified β-cyclodextrin, 105 parts of acetonitrile, 8 parts of polyethylene oxide, 0.15 parts of lithium perchlorate, and 0.9 parts of succinonitrile were mixed and stirred for 13 hours to obtain a mixed solution;

[0068] Step 3: Place the polyacrylonitrile fiber membrane into a polytetrafluoroethylene mold, add the mixed solution dropwise, dry and demould at 40°C to obtain a composite solid electrolyte.

[0069] Comparative Example 1: β-cyclodextrin is not modified, and the rest is the same as Example 4, specifically as follows:

[0070] Pre-preparation: The preparation process of modified polyacrylonitrile is:

[0071] (1) 10 parts of polyacrylonitrile, 110 parts of ethylenediamine and 500 parts of deionized water were mixed, heated to 70°C, and reacted for 12 hours to obtain amino polyacrylonitrile; (2) 8 parts of amino polyacrylonitrile, 4 parts of intermediate B, 50 parts of toluene and 1 part of aluminum chloride were mixed, heated to 50°C, and reacted for 6 hours to obtain modified polyacrylonitrile.

[0072] Step 1: 12 parts of polyacrylonitrile, 4 parts of modified polyacrylonitrile, and 120 parts of N,N-dimethylformamide were mixed, stirred for 15 hours, and placed in an electrospinning machine. The parameters were set as follows: voltage 15KV, needle and receiver 15cm, propulsion speed 0.3mL / h, drum speed 400r / min, temperature 30°C, to prepare a polyacrylonitrile fiber membrane;

[0073] Step 2: 0.6 parts of β-cyclodextrin, 105 parts of acetonitrile, 8 parts of polyethylene oxide, 0.15 parts of lithium perchlorate, and 0.9 parts of succinonitrile were mixed and stirred for 13 hours to obtain a mixed solution;

[0074] Step 3: Place the polyacrylonitrile fiber membrane into a polytetrafluoroethylene mold, add the mixed solution dropwise, dry and demould at 40°C to obtain a composite solid electrolyte.

[0075] Comparative Example 2: Polyacrylonitrile is not modified, and the rest is the same as Example 4, specifically as follows:

[0076] Pre-preparation: The preparation process of modified β-cyclodextrin is:

[0077] S1: Under nitrogen atmosphere, 10 parts of phosphorus oxychloride, 4 parts of pentaerythritol, and 40 parts of anhydrous acetonitrile were mixed, the temperature was raised to 72°C, and the reaction was carried out for 6 hours to obtain intermediate A;

[0078] S2: (1) 15 parts of intermediate A, 1 part of triethylamine and 50 parts of toluene were mixed and ultrasonically stirred for 4 hours to obtain a mixed solution of intermediate A; (2) 6 parts of polyethylene oxide were slowly added to the mixed solution of intermediate A, the temperature was raised to 70°C, and the reaction was carried out for 5 hours to obtain intermediate B;

[0079] S3: (1) Mix 12 parts of β-cyclodextrin, 1 part of triethylamine and 60 parts of distilled water, and stir ultrasonically for 2 hours to obtain a β-cyclodextrin mixed solution; (2) Mix 20 parts of intermediate B with 65 parts of toluene, and stir ultrasonically for 4 hours to obtain an intermediate B solution; (3) Heat the intermediate B solution to 80°C, slowly add the β-cyclodextrin mixed solution, and after the addition is complete, react for 4 hours to obtain modified β-cyclodextrin.

[0080] Step 1: 12 parts of polyacrylonitrile and 120 parts of N,N-dimethylformamide were mixed, stirred for 15 hours, and placed in an electrospinning machine. The parameters were set as follows: voltage 15KV, 15 cm between the needle and the receiver, propulsion speed 0.3 mL / h, drum speed 400 r / min, temperature 30°C, to prepare a polyacrylonitrile fiber membrane;

[0081] Step 2: 0.6 parts of modified β-cyclodextrin, 105 parts of acetonitrile, 8 parts of polyethylene oxide, 0.15 parts of lithium perchlorate, and 0.9 parts of succinonitrile were mixed and stirred for 13 hours to obtain a mixed solution;

[0082] Step 3: Place the polyacrylonitrile fiber membrane into a polytetrafluoroethylene mold, add the mixed solution dropwise, dry and demould at 40°C to obtain a composite solid electrolyte.

[0083] Comparative Example 3: β-cyclodextrin and polyacrylonitrile are not grafted with polyethylene oxide segments, and the rest is the same as Example 4, specifically as follows:

[0084] Pre-preparation: The preparation process of modified β-cyclodextrin is:

[0085] S1: Under nitrogen atmosphere, 10 parts of phosphorus oxychloride, 4 parts of pentaerythritol, and 40 parts of anhydrous acetonitrile were mixed, the temperature was raised to 72°C, and the reaction was carried out for 6 hours to obtain intermediate A;

[0086] S2: (1) Mix 12 parts of β-cyclodextrin, 1 part of triethylamine and 60 parts of distilled water, and stir ultrasonically for 2 hours to obtain a β-cyclodextrin mixed solution; (2) Mix 20 parts of intermediate A with 65 parts of toluene, and stir ultrasonically for 4 hours to obtain an intermediate A solution; (3) Heat the intermediate A solution to 80°C, slowly add the β-cyclodextrin mixed solution, and after the addition is complete, react for 4 hours to obtain modified β-cyclodextrin.

[0087] Pre-preparation: The preparation process of modified polyacrylonitrile is:

[0088] (1) 10 parts of polyacrylonitrile, 110 parts of ethylenediamine and 500 parts of deionized water were mixed, heated to 70°C, and reacted for 12 hours to obtain amino polyacrylonitrile; (2) 8 parts of amino polyacrylonitrile, 4 parts of intermediate A, 50 parts of toluene and 1 part of aluminum chloride were mixed, heated to 50°C, and reacted for 6 hours to obtain modified polyacrylonitrile.

[0089] Step 1: 12 parts of polyacrylonitrile, 4 parts of modified polyacrylonitrile, and 120 parts of N,N-dimethylformamide were mixed, stirred for 15 hours, and placed in an electrospinning machine. The parameters were set as follows: voltage 15KV, needle and receiver 15cm, propulsion speed 0.3mL / h, drum speed 400r / min, temperature 30°C, to prepare a polyacrylonitrile fiber membrane;

[0090] Step 2: 6 parts of modified β-cyclodextrin, 105 parts of acetonitrile, 8 parts of polyethylene oxide, 0.15 parts of lithium perchlorate, and 0.9 parts of succinonitrile were mixed and stirred for 13 hours to obtain a mixed solution;

[0091] Step 3: Place the polyacrylonitrile fiber membrane into a polytetrafluoroethylene mold, add the mixed solution dropwise, dry and demould at 40°C to obtain a composite solid electrolyte.

[0092] Testing experiment: (1) The composite solid electrolyte obtained in Example 4 and Comparative Examples 1-3 was subjected to a vertical combustion test according to GB / T 2408. After applying the flame to the sample for 10±0.5S, the flame was removed, the residual flame time was measured, and the vertical combustion level was used for rating; (2) The composite solid electrolyte obtained in Example 4 and Comparative Examples 1-3 was tested for the AC impedance of the sample using the EIS method, the test temperature was 30°C, and the ionic conductivity was calculated; (3) The composite solid electrolyte obtained in Example 4 and Comparative Examples 1-3 was prepared into a sample with a width of 15mm, placed on the fixture of a universal testing machine at room temperature, and stretched at a speed of 100mm / s to obtain the tensile strength. The measured data are shown in the following table:

[0093]

[0094] Table 1

[0095] Conclusion: Example 4 effectively improves the compatibility with the polymer matrix by modifying β-cyclodextrin, thereby improving the ionic conductivity and tensile strength of the composite solid electrolyte. At the same time, the spirocyclic phosphate groups grafted onto β-cyclodextrin also improve the overall flame retardancy of the composite solid electrolyte. Comparative Example 1 does not modify β-cyclodextrin, and its flame retardancy, conductivity and strength are reduced; Comparative Example 2 does not modify polyacrylonitrile, and its flame retardancy, conductivity and strength are reduced; Comparative Example 3 β-cyclodextrin and polyacrylonitrile are not grafted with polyethylene oxide segments, which reduces the compatibility with the matrix and the strength.

[0096] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

Claims

1. A process for preparing a flame retardant polyethylene oxide composite solid electrolyte, characterized in that: The following steps are involved: Step 1: Modified polyacrylonitrile, polyacrylonitrile and N,N-dimethylformamide are mixed, stirred for 12-15 hours, and placed in an electrospinning machine to prepare a polyacrylonitrile fiber membrane; Step 2: Mix the modified β-cyclodextrin, acetonitrile, polyethylene oxide, lithium perchlorate and succinonitrile, and stir for 12-15 hours to obtain a mixed solution; Step 3: Place the polyacrylonitrile fiber membrane into a polytetrafluoroethylene mold, add the mixed solution dropwise, dry and demould at 40°C to obtain a composite solid electrolyte.

2. The process for preparing a flame-retardant polyethylene oxide composite solid electrolyte according to claim 1, characterized in that: The preparation process of the modified β-cyclodextrin is: S1: Under a protective atmosphere, phosphorus oxychloride, pentaerythritol and anhydrous acetonitrile are mixed, the temperature is raised to 72-80°C, and the reaction is carried out for 6-8h to obtain intermediate A; S2: (1) Mix intermediate A, triethylamine and toluene, and stir ultrasonically for 4-5 hours to obtain a mixed solution of intermediate A; (2) Slowly add polyethylene oxide to the mixed solution of intermediate A, heat to 70-80° C., and react for 5-8 hours to obtain intermediate B; S3: (1) Mix β-cyclodextrin, triethylamine and distilled water, and stir ultrasonically for 1-2 hours to obtain a β-cyclodextrin mixed solution; (2) Mix intermediate B with toluene, and stir ultrasonically for 3-4 hours to obtain an intermediate B solution; (3) Heat the intermediate B solution to 75-80°C, slowly add the β-cyclodextrin mixed solution, and after the addition is complete, react for 3-4 hours to obtain modified β-cyclodextrin.

3. The process for preparing a flame-retardant polyethylene oxide composite solid electrolyte according to claim 2, characterized in that: The intermediate A comprises the following components: by weight, 10-12 parts of phosphorus oxychloride, 4-5 parts of pentaerythritol, and 40-50 parts of anhydrous acetonitrile; The intermediate B comprises the following components: by weight, 15-18 parts of intermediate A, 1-2 parts of triethylamine, 50-60 parts of toluene, and 6-8 parts of polyethylene oxide.

4. The process for preparing a flame-retardant polyethylene oxide composite solid electrolyte according to claim 2, characterized in that: The β-cyclodextrin mixed solution comprises the following components: by weight, 10-12 parts of β-cyclodextrin, 0.5-1 parts of triethylamine, and 50-60 parts of distilled water; the intermediate B solution comprises the following components: by weight, 15-20 parts of intermediate B and 60-65 parts of toluene.

5. The process for preparing a flame-retardant polyethylene oxide composite solid electrolyte according to claim 1, characterized in that: The preparation process of the modified polyacrylonitrile is as follows: (1) mixing polyacrylonitrile, ethylenediamine and deionized water, heating to 70-75° C., reacting for 12-15 hours, and obtaining amino polyacrylonitrile; (2) mixing amino polyacrylonitrile, intermediate B, toluene and aluminum chloride, heating to 50-55° C., and reacting for 6-8 hours, and obtaining modified polyacrylonitrile.

6. The process for preparing a flame-retardant polyethylene oxide composite solid electrolyte according to claim 5, characterized in that: The amino polyacrylonitrile comprises the following components: by weight, 10-12 parts of polyacrylonitrile, 110-120 parts of ethylenediamine, and 500-550 parts of deionized water; the modified polyacrylonitrile comprises the following components: by weight, 8-10 parts of amino polyacrylonitrile, 4-5 parts of intermediate B, 50-55 parts of toluene, and 1-2 parts of aluminum chloride.

7. The process for preparing a flame-retardant polyethylene oxide composite solid electrolyte according to claim 1, characterized in that: The working parameters of the electrospinning machine are: voltage 15-18KV, needle and receiver 15-20cm, propulsion speed 0.3-0.5mL / h, drum speed 400-450r / min, temperature 30-35°C, humidity 30%-40%.

8. The process for preparing a flame-retardant polyethylene oxide composite solid electrolyte according to claim 1, characterized in that: The polyacrylonitrile fiber membrane comprises the following components: by weight, 10-12 parts of polyacrylonitrile, 3-4 parts of modified polyacrylonitrile, and 100-120 parts of N,N-dimethylformamide.

9. The process for preparing a flame-retardant polyethylene oxide composite solid electrolyte according to claim 1, characterized in that: The mixed solution comprises the following components: by weight, 0.5-0.8 parts of modified beta-cyclodextrin, 100-110 parts of acetonitrile, 5-10 parts of polyethylene oxide, 0.1-0.2 parts of lithium perchlorate, and 0.8-1 parts of succinonitrile.

10. A composite solid electrolyte obtained according to the preparation process of a flame-retardant polyethylene oxide composite solid electrolyte according to any one of claims 1 to 9.

Citation Information

Cited By

  • Polymer-based solid electrolyte membrane, method for producing same, and solid

    CN121260902A

  • Solid-state battery, organic-inorganic composite solid electrolyte and preparation method thereof

    CN121460691A